Does mast seeding shape mating time in wild boar? A comparative study. (20th July 2022) - Cachelou, Jessica; Saint-Andrieux, Christine; Baubet, Eric; Nivois, Eveline; Richard, Emmanuelle; Gaillard, Jean-Michel; Gamelon, Marlène
Abstract : In seasonal environments, the timing of reproduction often matches with the peak of food resources. One well-known effect of global warming is an earlier phenology of resources, leading to a possible mismatch between the timing of reproduction for consumers and food peak. However, global warming may also change the dynamics of food resources, such as the intensity and frequency of pulsed mast seeding. How quantitative changes in mast seeding influence the timing of reproduction of seed consumers remains unexplored. Here, we assess how yearly variation in mast seeding influences mating time in wild boar ( Sus scrofa ), a widespread seed consumer species. We took advantage of the intensive monitoring of both female reproduction (1636 females) and acorn production over 6 consecutive years across 15 populations of wild boar in the wild. We found that mating time occurs earlier when acorn production increases in most but not all populations. In two out of 15 populations, heavy females mated earlier than light ones. Our findings demonstrate that mast seeding advances the mating time in some populations, which could perhaps impact how boars respond to climate change.